Analysis of Alfisol Soil Infiltration Rate on Various Land Cover and Its Effect on Soil Erodibility in Mount Bromo Special Purpose Forest Area, Indonesia - Maro'ah, Siti; Cahyono, Ongko; Ariyanto, Dwi Priyo; Pramudita, Tesalonika (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Plant canopies can protect the soil surface from raindrops and rooting activities that cause changes in biophysical properties. A low infiltration rate will reduce the soil’s capacity to store water to be low, resulting in a high soil erodibility value. This research aims to obtain infiltration values on different land cover, analyze the effect of land cover on soil infiltration rate, and analyze the effect of soil infiltration rate on soil erodibility. The research includes exploratory, descriptive research with a purposive sampling method. The study results show an increased soil infiltration rate can reduce soil erodibility. The infiltration rate of 74-year-old mahogany land cover ranged from 1.94–3.03 cm/hour, 50-year-old mahogany 1.61 cm/hour, old pine 1.53–1.89 cm/hour, old tapped pine 1.54–3.43 cm/hour, young pine 0.48–1.60 cm/hour, young pine 0.37–0.61 cm/hour, and 5-year-old sonokelling 0.56–0.73 cm/hour. The highest infiltration value is in 74-year-old mahogany and the lowest in young pine. The highest soil erodibility value is in young tapped pine and the lowest in 50-year-old mahogany. Erodibility is the sensitivity of soil to erosion. It is easier to erode if its erodibility value is higher; conversely, erosion is less likely to occur if its erodibility value is lower. An increase in soil infiltration rate can reduce soil erodibility. Keywords: Horton method, land cover, Mount Bromo, soil erodibility, soil infiltration rate